EVALUASI PELAKSANAAN PROYEK PENGUATAN PROFIL PELAJAR PANCASILA (P5) DI SD NEGERI KARANGDUREN 02 - Koko Wijayanto; Adi Winanto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to examine the context, input, process, and product of the implementation of the Strengthening the Profile of Pancasila Students (P5) program at SD Negeri Karangduren 02. Conducted comprehensively using the CIPP (Context, Input, Process, Product) evaluation model developed by Stufflebeam, this research is an evaluative study with a descriptive qualitative approach. Data were collected through in-depth interviews, document studies, and a Likert scale questionnaire as supporting evidence. The research subjects were the principal, 2 teachers (from upper and lower grades), and 4 students (2 from upper and 2 lower grades), selected using a purposive sampling technique. The results indicate that: (1) The context aspect was in the